Association of Serum Biomarkers With Post-Thrombolytic Symptomatic Intracranial Hemorrhage in Stroke: A Comprehensive Protein Microarray Analysis From INTRECIS Study - Cui, Yu; Zhao, Yong; Chen, Shao-Yuan; Sheng, Bao-Ying; Wang, Li-Hua; Meng, Wei-Hong; Chen, Hui-Sheng (Frontiers in Neurology, 2022)
Background: Symptomatic intracranial hemorrhage (sICH) after intravenous thrombolysis is closely related to poor outcome of stroke. Aims: Determine serum biomarkers associated with sICH based on INTRECIS study. Methods: Enrolled patients with sICH and without any ICH were matched by propensity score matching with the ratio of 1:1. Preset 49 biomarkers were measured by protein microarray analysis. Enrichment of Gene Ontology and pathway, and protein-protein interaction network were analyzed in the identified biomarkers. Results: Of consecutive 358 patients, 8 patients occurred sICH, which was assigned as sICH group, while 8 matched patients without any ICH were assigned as Non sICH group. A total of 9 biomarkers were found significantly different between groups, among which the levels of interferon (IFN)-γ and interleukin (IL)-4 were higher, while the levels of C-reactive protein (CRP), glial cell line-derived neurotrophic factor (GDNF), insulin-like growth factor binding protein (IGFBP)-6, lymphatic vessel endothelial hyaluronan receptor (LYVE)-1, matrix metalloprotein (MMP)-2, plasminogen activator inhibitor (PAI)-1, and platelet-derived growth factor (PDGF)-AA were lower in sICH group, compared with those in Non sICH group. Conclusions: Our finding indicated baseline serum CRP, GDNF, IFN-γ, IGFBP-6, IL-4, LYVE-1, MMP-2, PAI-1, and PDGF-AA levels were associated with post-thrombolytic sICH in stroke.